Microcredit Accessibility in Rural Households: Evidence from Indonesia - Danang Budi Santoso; Christopher Gan (Institute for Economic and Social Research, 2019)
Extant literature suggests that microcredit may improve borrowers’ social and economic welfare. This study aimed to investigate the microcredit accessibility of rural households in Indonesia. Binary Logistic regression was used to distinguish the characteristics of microcredit borrowers and non-borrowers, and the factors affecting the approval of microcredit application. Primary data was collected through a survey on 488 rural households in Bantul, Yogyakarta. The empirical results suggested that age, marital status and education attainment significantly affect the characteristics of clients and non-clients of microcredit. The results also revealed that age of borrowers, household income, interest rates, and loan duration are key determinants affecting microcredit accessibility. The implications of the findings were provided.